A place to hunt: some observations on access to wildlife resources in the western United States. Issue 5 (3rd September 2021) - Eliason, Stephen L.
ABSTRACT: Recreational hunting is facing a number of challenges in the twenty-first century. In this essay, I maintain the inability of hunters to find a good quality place to hunt is the most serious impediment to sport hunting in the Western United States, especially for big game species. Securing access to privately owned land can be difficult, while public land generally provides unlimited access. Issues that hunters experience with inaccessible private land as well as public land that is overrun with hunters are highlighted. If hunters are unable to have good hunting opportunities in terms of both land access and wildlife availability, decreased participation is inevitable. Several alternatives are identified that could improve the hunting experience and keep hunters interested in the activity.